Venous Thrombosis Comparison in Femoral versus Internal Jugular Catheterization for Hemodialysis - Haris Naeem, Waqar Ahmed, Mateen Akram, Abad-Ur-Rehman, Rabbia Rizvi, Samee Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vascular access for hemodialysis is typically achieved through arteriovenous fistulas (AVFs), arteriovenous grafts (AVGs), or central venous catheters (CVCs). Despite the "Fistula First" initiative, CVCs remain widely used due to their ease of insertion and immediate availability in urgent cases. Approximately 25% of dialysis patients in United States are using them. Objective: To compare the frequency of venous thrombosis in patients undergoing hemodialysis with femoral versus internal jugular double lumen catheterization. Methodology: This randomized controlled trial was conducted at Department of Nephrology, Shaikh Zayed Hospital Lahore from 8th March 2022 to 7th September 2022. One hundred twenty patients were randomly divided into two groups: Group A (femoral vein catheterization) and Group B (internal jugular double lumen catheterization), each consisting of 60 patients. Results: The mean age was 52.71±10.50 years. Venous thrombosis occurred in 9 (15%) in femoral catheterization (Group A) while internal jugular catheterization (Group B) had the incidence of 3 (5%), the difference between the two groups was not statistically significant (P<0.068). Conclusion: The venous thrombosis occurred in 7.5% of patients with femoral catheters and 2.5% with internal jugular catheters and internal jugular vein may be the preferred site for catheterization due to its lower thrombosis rate. Keywords: Hemodialysis, Venous Thrombosis, Femoral, Internal jugular